A comprehensive rat transcriptome built from large scale RNA-seq-based annotation. Issue 15 (4th August 2020) - Ji, Xiangjun; Li, Peng; Fuscoe, James C; Chen, Geng; Xiao, Wenzhong; Shi, Leming; Ning, Baitang; Liu, Zhichao; Hong, Huixiao; Wu, Jun; Liu, Jinghua; Guo, Lei; et al.
Abstract: The rat is an important model organism in biomedical research for studying human disease mechanisms and treatments, but its annotated transcriptome is far from complete. We constructed a R at T ranscriptome R e-annotation named RTR using RNA-seq data from 320 samples in 11 different organs generated by the SEQC consortium. Totally, there are 52 807 genes and 114 152 transcripts in RTR. Transcribed regions and exons in RTR account for ∼42% and ∼6.5% of the genome, respectively. Of all 73 074 newly annotated transcripts in RTR, 34 213 were annotated as high confident coding transcripts and 24 728 as high confident long noncoding transcripts. Different tissues rather than different stages have a significant influence on the expression patterns of transcripts. We also found that 11 715 genes and 15 852 transcripts were expressed in all 11 tissues and that 849 house-keeping genes expressed different isoforms among tissues. This comprehensive transcriptome is freely available at http://www.unimd.org/rtr/ . Our new rat transcriptome provides essential reference for genetics and gene expression studies in rat disease and toxicity models.